Enhanced EISCAT UHF backscatter during high-energy auroral electron precipitation - Schlatter, Nicola M.; Ivchenko, Nickolay; Sergienko, T; Gustavsson, Björn Johan; Brändström, B. U. E. (Annales Geophysicae, 2013)
Natural enhancements in the backscattered power of incoherent scatter radars up to 5 orders of magnitudes above the thermal backscatter are sometimes observed at high latitudes. Recently observations of enhancements in the backscattered power including a feature at zero Doppler shift have been reported. These enhancements are limited in altitude to tens of kilometers. The zero Doppler shift feature has been interpreted as a signature of electron density cavitation. Enhanced plasma lines during these observations have also been reported. We report on the first EISCAT UHF observations of enhanced backscattered radar power including a zero Doppler shift feature. The enhancements originated from two distinct and intermittent layers at about 200 km altitude. The altitude extent of the enhancements, observed during auroral high-energy electron precipitation, was < 2 km.